Introduction to Hijaiyah Letters for Early Childhood through the Development of “TAHU JARI” Book - Triyantono, Kis; Joko Raharjo, Tri; Rusilowati, Ani (Universitas Negeri Semarang, 2021)
The limited availability of innovative books as a learning medium in the introduction of hijaiyah letters in children makes learning less optimal. The letter is a symbol of sound, the letter hijaiyah that is, the Arabic alphabet starting from ا (alif) to ي (ya). This study aims to analyze the feasibility of Cerita Huruf Hijaiyah Berseri book (TAHU JARI) in the introduction to hijaiyah letters for children aged 3-4 years. The design of this research is Research and Development (R&D) with reference to the theory of Borg and Gall. The stages in this research include 1) preliminary research and data collection; 2) Planning 3) Design development; 4) preliminary field trials; 5) Revise the trial results. TAHU JARI was tried out in 3 stages, the initial trial involved 4 students, the second trial involved 8 students and the operational field trial involved 16 students. Data collection techniques using observation, interviews, and questionnaires. Data were analyzed using quantitative descriptive. The results showed that the results of the initial field trials were 82.5% (feasible). In the second trial, the percentage was 90% (feasible). The operational field trial phase, obtained 92.5%, it shows that the development of learning media for Cerita Huruf Hijaiyah Berseri book (TAHU JARI) can be an interesting medium in introducing hijaiyah letters to early childhood. The results of this study indicate that the TAHUJARI book is suitable for use in children, that children easily understand hijaiyah letters quickly.